Peran Ekologi Buddhis dalam Membentuk Kesadaran Lingkungan Umat Buddha: Studi Pustaka Kualitatif - Dahlia Dahlia (Jurnal Budi Pekerti Agama Buddha, 2025)
Human life is highly dependent on a balanced relationship with both the natural and social environment. However, environmental degradation caused by human greed, uncontrolled exploitation of natural resources, and unsustainable consumption patterns has led to widespread ecological crises across various parts of the world. This study aims to examine in depth how ecological values embedded in Buddhist teachings can foster strong environmental awareness, particularly among Buddhist communities. Using a qualitative literature review method, the study systematically analyzes various textual sources, including Buddhist scriptures, classical literature, and contemporary ecological literature. The findings indicate that Buddhist teachings, which emphasize the principles of interdependence, moral ethics, mindfulness, and respect for all living beings, can cultivate attitudes of care and responsibility toward the environment when these values are consistently integrated into education from an early age, both within families, schools, monasteries, and the broader community. This study makes a significant contribution to the discourse on religion-based ecological ethics by positioning Buddhist ecology as a conceptual framework for the sustainable and profound transformation of ecological consciousness.